Impact of personality traits on work performance in tidal paddy production in the Gambia: a review - Hassan, Salim; Sanyang, Demba; Asmuni, Azizan; Sanyang, Saikou E. (International Organization of Scientific Research, 2017)
Efficient personality is central for effective work performance in tidal paddy farming. Improve rice productivity in the Gambia is essential for stakeholders as it is main actor in achieving food self-sufficiency and security. The aim of this paper is to confirm the impact of personality traits on work performance. Furthermore, to determine the relation between the personality traits for the paddy farmers with work performance; and also to identify the strength of the traits relation with work performance for paddy farmers. This paper uses previous works on personality traits, work performance, and its related studies and looked at how the seven personality traits (willingness to take risks, information seekers, problem solving ability, willingness to spend on capital, extensive network of information, dare to make decisions, and highly disciplined) of paddy farmers and work performance can be used to boost urban food supply through rice production. The need for appropriate development programs is required as one of the options to generate income and improve livelihood of farmers in developing countries.